(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Magnetic Resonance Venography (MRV) is a non-invasive method that evaluates the venous system without exposure to the radiation in the procedure compared to cerebral angiography and CT Venography. Nowadays, the use of MRV cerebral started to increase even though there are still many nonvisualized (not visualized vein image) on MRV led to divergent interpretations or noncompliance to the findings of cerebral angiography, which is the gold standard to evaluate venous system. There has been few research comparing MRV findings with cerebral angiography so far. Objective: The aim of this study is to evaluate the findings of non-visualized on MRV compare to cerebral angiography as the gold standard in helping the interpretation of examinations to avoid misdiagnosis. Methods: Observational retrospective analytic study was used in this study that conducted at Husada Utama Surabaya Hospital from October 2013 to February 2014. 39 out of 49 patients selected as samples for fulfilling the inclusion criteria. The observation on the results of MRV and cerebral angiography procedures performed by two specialists of radiology, then the data were analyzed using SPSS. Results: Based on the findings of abnormalities location from 39 samples, we found 35.45% abnormalities in the transverse sinus, 32.91% in the sigmoid sinus, 27.84% in the jugular vein, 2.53% in the straight sinus, and 1.27% in the superior sagittal sinus.The results of comparison between MRV test and cerebral angiography showed compliance at 21% hypoplasia with 88.9% of thrombus. MRV test results with the cause of hypoplasia have100% sensitivity, 67.4% specificity, and 70% accuracy.Meanwhile, we found that 41% sensitivity, 82% specificity, and 50% accuracy because of thrombus. Conclusion: There was significant compliance between 3D-TOF MRV cerebral findings along with cerebral angiography, especially at thrombus.